Prevalence of work-related musculoskeletal disorders among IT professionals in India-a literature review - Singh, Ritika M.; Borkar, Pradeep (International Journal of Research in Medical Sciences, 2020)
Musculoskeletal disorders are typically characterised by discomfort (often persistent) and restrictions in mobility, dexterity and functional ability, reducing people’s capability to work and participate in social roles with associated influences on psychological welfare, and at a wider level influence on the prosperity of communities Information technology- has played a vital role in transforming India from a slow administrative economy into a land of innovational entrepreneurs. The aim of this review is to, critically analyze the literature and report on the prevalence of work-related musculoskeletal disorders in information technology professionals. The review focused on computers users and software professionals. An extensive literature search was undertaken using google scholar and PubMed databases for last 10 years from 2011 to 2020. Further Following a thorough search of the databases, a total of 25 articles were evaluated. A number of articles reported a high prevalence of MSD, generally various studies have been done on information technology professionals and related to the work of IT professionals and studies on various risk factors also have been done in different states of India. 17 articles had selected for the study purpose in which prevalence study had selected for the review. The prevalence among the IT professionals is not uniform; however, Software engineers and computer operators appear to be more prone to neck, shoulder and back pain.